Avaliação de desempenho de uma rede wi-fi doméstica, usando ferramenta de análise de tráfego - SANTOS, Lucas Sousa dos (2023)
This study describes the main characteristics of the fixed broadban wireless network, more commonly known as wi-fi, explaining in a clearer way how to understand its operation and how to be able to analyze the data traffic that is being transmitted by the internal network, targeting the vast majority of the population, that is, any common or domestic user has the ability to carry out this analysis.